INFLUENCE OF FINGOLIMOD ON NON-RESPIRATORY FUNCTIONS OF LUNGS IN ANTIPHOSPHOLIPID SYNDROME - Мария Анатольевна Уракова; Ирина Георгиевна Брындина (Медицина в Кузбассе, 2021)
Objective – the role of immunosuppressive mechanisms in the correction of respiratory system dysfunctions associated with autoimmune pathology (antiphospholipid syndrome).